SOCIAL MEDIA MARKETING STRATEGY IN BUILDING CUSTOMER BRAND AWARENESS AT THE GRAND CENTRAL MEDAN HOTEL - Petrus Lajor Ginting; Endang Sulistya Rini; Sugih Arto Pujangkoro (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2024)
This research was conducted to analyze the strengths, opportunities, aspirations and results related to the social media marketing strategy used at the Grand Central Medan hotel to build customer brand awareness. This research uses the SOAR analysis method, which is a method that companies can use to create a marketing strategy planning framework to face business competition by analyzing internal and external factors using the IFAS and EFAS matrices. This research uses qualitative data methods, namely data obtained by collecting data sources through interviews and observations as well as collecting documents from existing journals and various other accurate internet sources. The results of this research show that based on the IFAS matrix the value is 3.75 and the EFAS value is 3.16. This strategy emphasizes 1. Creating content and paying attention to when to post content that interests visitors; 2. Strategy to increase promotion and cooperation; 3. Strategy to provide attractive promotions and incentives for employees.